IMPLEMENTATION OF LEARNING FROM HOME PROGRAM DURING THE COVID-19 PANDEMIC IN KENDARI CITY - Sitti Rahmaniar Abubakar; Nanang Sahriana (Universitas Ahmad Dahlan, 2021)
The formulation of the problem in this research is how the implementation of the learning from the home program during the Covid-19 pandemic in Kendari City. The research objective was to describe the implementation of the learning from the home program during the Covid-19 pandemic. This type of research is qualitative research, namely research that describes conditions that occur in the field qualitatively. The research subjects were Kindergarten teachers in Kendari City who taken purposively. The data analysis technique is descriptive with data collection techniques, namely interviews and document study. The results of the study found that Kindergarten teachers in Kendari City implemented learning from the home program during the Covid-19 pandemic by taking the following steps: (1) making weekly and daily learning plans, (2) implementing learning programs for children from home, (3) assessing child development in collaboration with parents, and (4) conducting feedback and discussions with parents. The study concludes that Kindergarten teachers in Kendari City implemented learning from the home program during the Covid-19 pandemic by the learning steps in Permendiknas Number 137 of 2014 by implementing health protocols.